Hiroshima : the last witnesses - Sheftall, M. G. (Mordecai G.) (Sheftall, M. G. (Mordecai G.). Embers, 2024)
"The first volume in a two-book series about each of the atomic bomb drops that ended the Pacific War based on years of irreplicable personal interviews with survivors to tell a story of devastation and resilience"--